HITUNG LEUKOSIT PADA KETUBAN PECAH DINI SEBAGAI INDIKATOR INFLAMASI DI RUMAH SAKIT UNIVERSITAS AIRLANGGA TAHUN 2015 - Iqsyadina Fikriya, NIM011411223004 (2016)
Background : Premature Rupture of Membrane (PROM) is a complication of pregnancy that spontaneous rupture of the membranes before the onset of labor. PROM is one of the complications of pregnancy and childbirth that require attention, because the prevalence is sizable. Approximately 10% of pregnant women will experience KPD. In Indonesia, KPD occurred at about 6.46 to 15.6% in term pregnancies. Premature rupture of membranes is closely related to increased levels of leukocytes relation to the inflammatory process. Objectives : the objective of this study is to analyze the the difference of leukocyte count through the DL test results in pregnant women with and without PROM and shows the optimal cut-off point of leukocyte count in pregnant women with PROM Methods : This study is a diagnostic test using comparative design. This research used the medical records of patients with PROM and non-PROM at Airlangga University Hospital in period of January to Desember 2015. Descriptive analysis and bivariate analysis using Independent T-test was done on some specific variables. The limit of significances was p <0.05 with 95% confidence interval. This research analyze the cuf-off point of leukocytes count with the best sensitivity, specificity. Result : The results of Independent T-test showed there is significant difference of leukocytes count between PROM and non-PROM. The limit of leukocytes count between PROM and non-PROM in Airlangga University Hospital is on cut off point ≥ 9,53 . 103 /μl with sensitivity 76,6%, specificity 76,6%, ROC 0,88. Conclusion : The leukocytes count at a certain value can be used as the important supporting diagnosis to compare PROM from non-PROM in aterm pregnancy, so that it will be easier to determine the therapy.